"No boots on the ground": the effectiveness of US drones against Al Qaeda in the Arabian Peninsula. Issue 2 (3rd April 2018) - Bolland, Thomas; Lee Ludvigsen, Jan Andre
ABSTRACT: The number of US drone strikes against Al Qaeda in the Arabian Peninsula (AQAP) in Yemen has increased significantly since 2010, but received limited academic attention. This article examines the effectiveness of this drone campaign using an existing theoretical framework. Crucially, we contribute to the framework by adding a fourth intervening variable, namely target correspondence. Through a single case study, it is found that drones have only enjoyed limited success in degrading AQAP's hierarchical structure, qualified human resources and access to key material resources, and in some cases – owing to our target correspondence analysis – this limited success has come at a price. It is found that drones have temporarily disrupted AQAP by successfully eliminating senior leaders involved in coordinating and overseeing external operations. Overall, AQAP's ability to hit Western targets remains significant.